Application of Scaffolding Method To Improve Learning Outcomes Of The Material On Praiseable Morals at MTS Masyarqul Anwar Mekar Jaya Tanjung Raja - Sitini, Yuda (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the application of the scaffolding method in improving learning outcomes of commendable moral material at MTS Masyarqul Anwar Mekar Jaya Tanjung Raja. The scaffolding method is a learning approach that provides gradual support to students until they are able to learn independently. In this study, the scaffolding method was applied through several stages, namely identifying students' proximal development zones, providing initial support, discussion and reflection, providing gradual challenges, and evaluation and reinforcement. The results of the study showed that this method was effective in improving understanding and application of commendable moral values, such as honesty, patience, and responsibility. In addition, this method also contributes to increasing students' learning motivation and building their confidence in making decisions based on moral values. Therefore, the scaffolding method is recommended to be applied in moral learning in order to form better student character.